PENGEMBANGAN MEDIA DIGITAL SMART BOOKLET MENGGUNAKAN STRATEGI STORY MAPS UPAYA PENINGKATAN MEMBACA PEMAHAMAN SISWA KELAS III SD NEGERI PULOSARI 1 - Nashikhah, Maftukhatun; SB, Nugraheti Sismulyasih (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Reading comprehension is one of the keys to student success in following the learning process, but it provides great challenges that have the potential to cause problems for elementary school students. The purpose of this study is to develop, test the feasibility and test the effectiveness of smart booklet digital media using the story maps strategy to improve reading comprehension of grade III elementary school students. This research uses Sugiyono's Research and Development (R&D) method which is modified into 8 stages including potentials and problems; data collection; product design; design validation; design revision; product trials; product revision; and trial use. The results of the assessment of media experts of 95% and material experts of 95% of the criteria are very feasible. The results of the class teacher's response of 92.85% and the student's response of 94% of the criteria were very feasible. The media effectiveness test using the T test obtained a significance value of 0.000. The results of the N-Gain calculation obtained a value of 0.6219 medium criteria. Therefore, smart booklet digital media using the story maps strategy can be said to be very feasible and effective to be applied in improving reading comprehension.